Increasing reproductive health literacy among adolescent females in Islamic boarding schools through peer education - Lu'lu Nafisah; Yuditha Nindya Kartika Rizqi; Aisyah Apriliciciliana Aryani (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
The importance of reproductive health education in Islamic boarding schools is often overlooked. Whereas the prevalence of reproductive health issues among teenage females in Islamic boarding schools remains high, including anemia, vaginal discharge, dysmenorrhea, premenstrual syndrome, and personal hygiene. These difficulties have an impact such as absenteeism at school, wasting and infertility. Peer education is seen to be capable of addressing these issues since adolescents in Islamic boarding schools engage with their peers more frequently than with their families, instructors, or health workers. The purpose of this activity is to increase participants' knowledge, attitudes, and skills on peer education and adolescent reproductive health. Adolescent reproductive health education, peer education training, and assistance in extracurricular activities that have the potential to help establish healthy madrasas are among the activities carried out. Thirty students who wanted to become peer educators took part in this activity. The results of the activities were evaluated using pre-test and post-test questionnaires, as well as the practice of health education and counseling. The result of this activity is an increase in participants' knowledge about adolescent reproductive health by 8.28 and peer education by 5.17 after participating in the activity. Participants are also able to recognize reproductive health issues that commonly arise in teens and how to prevent them.